1993
DOI: 10.1002/jcb.240530310
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of vesicular carriers during differentiation and synapse formation

Abstract: Coated and noncoated vesicles participate in cellular protein transport. Both acetylcholine receptors (AChR) and acetylcholinesterase (AChE) are transported via coated vesicles, some of which accumulate beneath the neuromuscular synapse where AChRs cluster. To investigate the mechanisms by which these proteins are transported during postsynaptic remodeling, we purified coated vesicles from the bovine brain via column chromatography (Sephacryl S-1000) and raised monoclonal antibodies to epitopes of the vesicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 62 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…Clathrin coated vesicles were isolated and purified from bovine brains as described previously [Bursztajn et al, 1993]. Briefly, brains were homogenized in a Waring blender with three high speed 10 s bursts in two volumes of Buffer A [(0.1 M 2-N-morpholino acid (MES), 0.5 mM MgC1 2 , 1 mM ethylene glycol bis (␤aminoethyl ether)-N,N 1-tetra acetic acid (EGTA), 0.02% NaN3, pH 6.5].…”
Section: Materials and Methods Coated Vesicle Preparation Enriched Fomentioning
confidence: 99%
See 4 more Smart Citations
“…Clathrin coated vesicles were isolated and purified from bovine brains as described previously [Bursztajn et al, 1993]. Briefly, brains were homogenized in a Waring blender with three high speed 10 s bursts in two volumes of Buffer A [(0.1 M 2-N-morpholino acid (MES), 0.5 mM MgC1 2 , 1 mM ethylene glycol bis (␤aminoethyl ether)-N,N 1-tetra acetic acid (EGTA), 0.02% NaN3, pH 6.5].…”
Section: Materials and Methods Coated Vesicle Preparation Enriched Fomentioning
confidence: 99%
“…Because previous studies have shown that coated vesicles contain AChRs and AChE [Bursztajn and Fischbach, 1984;Porter-Jordon et al, 1986;Bursztajn et al, 1991], we collected 3 ml fractions, tested for acetylcholinesterase [Ellman et al, 1961], hexosaminidase [Hall et al, 1978], and NADH cytochrome C reductase [Mahler, 1955] activities, and pooled the fractions enriched in protein and AChE activity but low in hexosaminidase (a marker for lysosomes) and NADH cytochrome C reductase (a marker for mitochondria) activities. Column chromatography revealed two peaks, one of which was enriched in protein and AChE activity [Bursztajn et al, 1993]. After obtaining a single peak from the second chromatography, we centrifuged it for 1 h at 34,000 rpm using a Beckman Type 35 rotor, and assessed the purity of the pellet of coated vesicles so obtained by SDS-polyacrylamide gel electrophoresis [Laemmli, 1970] and electron microscopy [Bursztajn et al, 1993].…”
Section: Materials and Methods Coated Vesicle Preparation Enriched Fomentioning
confidence: 99%
See 3 more Smart Citations